(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Lukman, Dinarti D, Siregar UJ, Turjaman M, Sudarsono. 2022. Characterization and identification of agarwood-producing plants (Aquilaria spp.) from North Aceh, Indonesia, based on morphological and molecular markers. Biodiversitas 23: 4861-4871. Agarwood is one of the non-timber export commodities important as raw materials for bioindustry. There are 26 agarwood-producing plant species in Indonesia belonging to three families (Thymelaeaceae, Euphorbiaceae, and Fabaceae). This study aims to identify the agarwood-producing plant species in North Aceh District, Aceh Province, Indonesia, based on their morphological and molecular characters. The evaluated morphological characteristics include the bark and leaf structures of endemic plants. Molecular characterization was carried out by sequencing of matK, ITS, and trnL-trnF genes. The collected data were analyzed using the appropriate software, such as R software, BlastX, Geneious Prime and MEGA X. The evaluated 66 accessions were clustered into two major groups based on their morphology. Group 1 consisted of 10.61% of the evaluated accessions is identified as Aquilaria beccariana. Group 2 was further classified into two subclusters (Group 2a and 3b). Group 2a consisted of 10,61% of the accessions as A. malaccensis and Group 2b consisted of 78,79% of the accessions as A. microcarpa. All samples are identified as A. malaccensis based on the matK DNA sequences. Meanwhile, Groups 1 are identified as A. beccariana and Group 2a and 2b as A. microcarpa based on the ITS sequences. Based on the trnL-trnF sequences, Groups 1 and 2a was identified as A. malaccensis and Group 2b as A. microcarpa.